Matematică
teocarina
2015-11-07 17:33:24
Calculati a) (x+3) - (x+3) b) (2x-1)² + 4x c) 7x (x+1) - 3x (x-1) - 2x d) ( 2x +1 )² - ( 2x -1)² Va rog!
Răspunsuri la întrebare
mihaelamimi76
2015-11-07 20:52:34

a) (x + 3) - (x + 3) = x + 3 - x - 3 = 0 b) (2x - 1)² + 4x = 4x² - 4x + 1 + 4x = 4x² + 1 c) 7*(x + 1) - 3* (x - 1) - 2x = 7x + 7 - 3x + 3 - 2x = 2x + 10 = 2(x + 5) d) (2x + 1)² - (2x - 1)² = 4x² + 4x + 1 - 4x² + 4x - 1 = 8x

brazy50cent
2015-11-07 20:53:49

a) (x+3) - (x+3)=x+3-x-3=0 b) (2x-1)² + 4x=4x²-2·2x+1+4x= 4x²-4x+1+4x=4x²+1 c) 7× (x+1) - 3× (x-1) - 2x= 7x+7-3x+3-2x=2x+10 d) ( 2x +1 )² - ( 2x -1)²= 4x²+2·2x+1-(4x²-2·2x+1)= 4x²+4x+1-4x²+4x-1=8x

Adăugați un răspuns